Meningkatkan Iklim Keamanan Sekolah dan Literasi Digital Untuk Mengoptimalkan Kurikulum Merdeka Belajar di SD Negeri 2 Petandakan (Educemara: Jurnal Pengabdian Masyarakat, 2024)
The current independent curriculum is one of the government's efforts to accelerate the process of changing education in Indonesia for the better. In improving its implementation, in addition to understanding the teacher as the main actor implementing the curriculum, it is necessary to create school safety so that schools are created that are safe, comfortable and fun. This dedication article will explain the results of the implementation of In House Training (IHT) at SD Negeri 2 Petandakan, Buleleng Regency, Bali. Implementation through the provision of material regarding digital literacy and school safety material both supporting facilities and how to maintain school security, creating schools that are safe, comfortable and fun. At the end of the activity, a reflection is held. The reflection activity is carried out by filling out the reflection instrument. The results of reflection show that most teachers experience limited time constraints in making security facilities, supervising all students to create a safe, comfortable and enjoyable school. The most challenging activity in school security activities is the simulation of student safety at school.
Keywords: Keywords: School Safety Climate, Digital Literacy, Merdeka Belajar Curriculum